Artistic Research: Charting a Field in Expansion - Assis, Paulo de; D'Errico, Lucia (London Rowman & Littlefield International, 2019)
This important new book explores the thriving field of practice-based artistic research from a theoretical point of view. It presents a comprehensive overview of artistic research in the context of specific artistic practices, ideal for graduate and postgraduate students, as well as to scholars, researchers and artists alike.This book represents a primer on artistic research, presenting diverse perspectives, strategies, methodologies, and concrete examples of research projects situated at the crossroads of art and academia. Exposing international work of significant research projects from Europe, Asia, Australia, South- and North America, it provides a multidisciplinary overview on different discourses and practices, exploring cutting-edge questions coming from the burgeoning field of artistic research. The first part includes chapters on artistic research and diverse artistic fields, addressing a common thread of questions and problematics. The second part provides insights into six internationally relevant artistic research projects. The comprehensive editors introduction offers a much-needed and extensive overview practice-based artistic research in general. Ideal for graduate students across Philosophy, Cultural Studies, Art, Music, Performance Studies and more, The book is enhanced by a range of multimedia components (images, videos, sounds).
Introduction / Paulo de Assis and Lucia D'Errico -- Theses on the Concept of Research / Jae Emerling -- Expositionality / Michael Schwab -- The Research Catalogue Exposition as a Digital Object: Challenges and Future / Luc Döbereiner -- Transpositions [TP] Artistic Data Exploration: Feed-back and Amplification / Cecile Malaspina -- SymbioticA: Interruptions in the Brain / Darren Jorgensen and David Savat -- Artistic Research in an Expanding Field: The Case of BioArt / jan jagodzinski -- Artistic Research and Sound Art in Public Urban Spaces / Marcel Cobussen -- Artistic Research and Music Technology / Jonathan Impett and Juan Parra -- Design Research in Architecture, Revisited / Murray Fraser -- Artistic Research and Performance / Laura Cull Ó Maoilearca -- Artistic Research as Participant Perception: Reflecting on the Project Computer Signals from an Arts-Inspired STS-Perspective / Priska Gisler -- A Laboratory for Performance Practice: The Case of MusicExperiment21 / Veerle Spronck -- Artistic Research and Musical Performance / Mieko Kanno -- Fantasies Finding Realities: The ConNext Network as a Case Study of the Evolution of an Artistic Research Dimension in Conservatories / Bernard Lanskey, Shu Chen Ong, and Abigail Sin -- Philosophy AS Artistic Research. Artists-Philosophers / Arno Böhler -- Notes on Contributors